Carabidae (Insecta: Coleoptera) from the Baja California Peninsula: checklist and new records for Mexico - Cerón-Gómez, Rafael; Márquez, Juan (Zootaxa, 2025)
An updated checklist dedicated to the family Carabidae for the Baja California Peninsula, Mexico, is presented, summarizing the current state of knowledge regarding its distribution and species richness. This compilation is based on an exhaustive review of specialized literature, consultation of databases and examination of specimens from entomological collections. A total of 152 taxa, belonging to eight subfamilies, 27 tribes, 64 genera, 132 species and 20 subspecies are reported. This study adds three first records for Mexico (Stenolophus limbalis LeConte, 1857, Pterostichus illustris LeConte, 1851 and Pterostichus jacobinus Casey, 1913), and eight first records for the peninsula, along with new distribution data for 16 species in the region. A regional distribution map of the first records is shown and priority collection areas for the future are discussed. This work aims to establish a baseline that serves as a reference for future taxonomic, ecological, conservation and biogeographic studies on the Baja California Peninsula and in Mexico.